An Evaluation of Performance in Educational Management at Dayah Darul Fallah, North Aceh - Bernoully; Manumanoso Prasetyo, Muhammad Anggung; Arianto, Sofyan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aims to analyze the implementation of performance evaluation in educational management at Dayah Darul Falah, Dewantara Subdistrict, North Aceh Regency. Performance evaluation is an essential tool in improving the quality of education, particularly in assessing the performance of teachers and educational staff. This research employs a descriptive qualitative approach, utilizing data collection techniques through in-depth interviews, participatory observation, and document analysis. The research participants include the headmaster, teachers, and educational staff involved in the performance evaluation process at Dayah Darul Falah. The collected data were analyzed using thematic analysis to identify patterns, themes, and meanings within the performance evaluation processes implemented. The findings indicate that Dayah Darul Falah applies various types of performance evaluation, including traditional evaluation, 360-degree evaluation, and competency-based evaluation. These evaluation processes aim to enhance the quality of teaching, motivation, and the professional development of teachers and staff. The performance evaluation conducted in a systematic and objective manner has proven to contribute to improving individual and institutional performance. This study contributes to the development of educational management in Islamic educational institutions, with recommendations for improving and optimizing the existing performance evaluation system to enhance the effectiveness of teaching in the future.